Pengaruh Media Interaktif Terhadap Minat Belajar Keterampilan Dasar Tenis Meja Siswa Sekolah Dasar - Fariz Fuad Fadillah; Mochamad Ridwan; Sapto Wibowo (Universitas Galuh, 2026)
This study aims to determine how the use of interactive media impacts students' learning interest in elementary school. This study used a quantitative one-group pretest-posttest model with a pre-experimental design. Elementary school students who served as the study subjects received interactive learning treatments. Data was gathered using a learning interest questionnaire both before and after the therapy. The data was examined for normality and hypothesis testing using a paired sample t-test. The findings demonstrated that using interactive media raised students' motivation to study. Interactive media can enhance the learning experience, increase student engagement, and foster a positive attitude towards learning activities. During learning, students became more active, engaged, and more attentive. The results of the study concluded that interactive media can increase elementary school children's learning interest and can be utilized as a differentiated teaching strategy to improve the quality of learning.